Autonomus Motivation as a Mediator Between an Empowering Climate and Enjoyment in MAle Volleyball Players - Mosqueda Ortiz, Sofía; López Walle, Jeanette M.; Gutiérrez García, Pablo; García Verazaluce, Juan; Trisitán, José (Multidisciplinary Digital Publishing Institute, 2019)
The objective of this work was to analyze a mediation model concerning the perception ofan empowering climate generated by a coach and enjoyment through the autonomous motivation ofathletes. The sample consisted of 71 elite male volleyball players from six countries. The age rangewas 14 to 18 years (M=16.5, SD=0.96). The relationships between the perception of an empoweringclimate, autonomous motivation, and enjoyment were positive and significant. The mediation modelshowed that autonomous motivation acts as a mediator in the relationship between the perception ofan empowering climate generated by the coach and the enjoyment reported by the athletes.